Mower County Aerial Survey 1949 Frankford Township Sections 11 and 12; Racine Township Sections 1 and 2; 3f69 (Mower County Historical Society, 1303 Sixth Avenue SW, Austin, MN 55912; www2.smig.net/mchistory)
1be363287cdbec4b30f02ab0c60336e9
United States
Minnesota
Mower
Frankford Township; Racine Township; Hamilton
Bear Creek
Keywords: Frankford Township Sections 11 and 12; County Road 2; Federal Highway 63; Rural School District 35; Chicago Great Western Railroad; agriculture; Racine Township Sections 1 and 2; Federal Highway 63; Chicago Great Western Railroad; agriculture; Agriculture